Analyzing Factors Affecting the Use of Voluntary Disclosure Information using a Modified Theory of Reasoned Action: A Study in Indonesia - Gunawan Wibisono; Devie Dwi Aryani Putri (The Indonesian Journal of Accounting Research, 2018)
Abstract: Voluntary disclosure information has been a research topic for a long time. However, very few tried to explain it from the investors' point of view. This study attempted to justify the use of voluntary disclosure information by using a modified Theory of Reasoned Action (TRA) model by adding perceived freedom of physical effort as a third behavior beliefs construct.  By using SEM and path analysis, this study found that all three behavior beliefs constructs affect behavior intention to use voluntary disclosure information. Perceived usefulness and perceived freedom of physical effort have a direct effect on behavior intention in using voluntary disclosure information while perceived ease of use is having an indirect impact to behavior intention in using voluntary disclosure information through perceived usefulness. This study has opened a path to a new view of research in voluntary disclosure topic, which is the information-seeking behavior from the investors' point of view. Further study related to this new view can be done to further extend the TRA model in particular to voluntary disclosure information settingAbstract: Pengungkapan informasi sukarela telah menjadi topik penelitian untuk waktu yang lama. Namun, sangat sedikit yang mencoba menjelaskannya dari sudut pandang investor. Penelitian ini berusaha untuk membenarkan penggunaan informasi pengungkapan sukarela dengan menggunakan model Theory Reasoned Action (TRA) yang dimodifikasi dengan menambahkan kebebasan yang dirasakan dari usaha fisik sebagai konstruk keyakinan perilaku ketiga. Dengan menggunakan SEM dan analisis jalur, penelitian ini menemukan bahwa ketiga konstruk keyakinan perilaku mempengaruhi niat perilaku untuk menggunakan informasi pengungkapan sukarela. Dirasakan kegunaan dan kebebasan yang dirasakan dari upaya fisik memiliki efek langsung terhadap niat perilaku dalam menggunakan informasi pengungkapan sukarela sementara persepsi kemudahan penggunaan memiliki dampak tidak langsung dengan niat perilaku dalam menggunakan informasi pengungkapan sukarela melalui kegunaan yang dirasakan. Studi ini telah membuka jalan untuk pandangan baru penelitian dalam topik pengungkapan sukarela, yang merupakan perilaku pencarian informasi dari sudut pandang investor. Studi lebih lanjut terkait dengan pandangan baru ini dapat dilakukan untuk lebih memperluas model TRA khususnya untuk pengaturan informasi pengungkapan sukarela.